The Micro-flora of gills, gut and skin of European eels (Anguilla anguilla) in lakes of Latvia - Strazdiņa, Vita; Terentjeva, Margarita; Valciņa, Olga; Eizenberga, Inga; Novoslavskij, Aleksandr; Ošmjana, Jevgēnija; Bērziņš, Aivars (2015)
The microbial contamination of fish is the most important factor in assurance of food safety. The microflora on the surface of skin, gills and gut of fish is constantly under the influence of the water environment and this may support colonization of fish by microorganisms. The goal of this study was to evaluate the bacterial contamination level on the skin, gills and in the gut of the European eel (Anguilla anguilla) detecting TBC and Enterobacteriaceae counts, as well as Listeria spp. and Salmonella spp. in freshly caught fish. Among the three lakes TBC on skin, gills and gut varied from 0.66 to 4.93, from 0.40 to 5.51 and from 0.30 to 6.37 CFU cm-2 , respectively. Enterobacteriaceae count on skin, gills and gut was from 0.00 to 4.30, from 0.00 to 2.47 and from 0.00 to 1.72 CFU cm-2 , respectively. The highest mean count of TBC in gills, skin and gut was found in samples from Sīvers lake, while the lowest in samples from Alūksnes lake and differences were significant (P < 0.05). Also the highest mean counts of Enterobacteriaceae were found on gills and skin of eels from Sīvers lake, but the highest count in gut was found in Usmas lake. All tested samples were Listeria monocytogenes and Salmonella spp. negative 0/31 (0). TBC and Enterobacteriaceae counts of skin, gills and gut were typical for wild fish in clear water. Foodborne pathogens as Salmonella spp. and Listeria monocytogenes have not been found in the present study indicating that fish are safe for human consumption.